Epidemiological investigations into factors associated with hock lesions, lameness and fertility in dairy cattle - Lim, Poh Ying (2014)
An investigation of 5186 hock maps, from 3691 cows with hair loss on the hocks from 76 UK dairy farms, identified six risk factors associated with area of hair loss: higher locomotion score; poor cleanliness; higher mean milk yield; low body condition score, prolonged winter housing and certain combinations of stall base and bedding materials. Another finding was significantly poor correlation between a categorical scale and the continuous measure of hair loss.